DEVELOPMENT OF A COULOMETER AT THE NATIONAL METROLOGY INSTITUTE OF COLOMBIA: DETERMINING THE AMOUNT OF SUBSTANCE CONTENT OF POTASSIUM HYDROGEN PHTHALATE - Smith-Osorio, Jessica; Castillo, Andrés; Torres-Quezada, Henry; Sandoval-Rojas, Andrea; Ágreda, Jesús; Torres Quezada, Henry; Castillo Forero, Andres Mauricio (Sociedade Brasileira de Quimica (SBQ), 2024)
Coulometry is a well-established technique for certified reference materials (CRM). However, commercial coulometers are currently expensive and utilize outdated software. The National Metrology Institute of Colombia (INMC) has developed a cheaper and modular coulometer with powerful software capable of controlling the instrument, and acquiring pH, the potential difference between generator electrodes, and the electrical current at any stage of the coulometric titration. The results obtained from this new coulometer align well with the novel method for calculating the amount of substance content of potassium hydrogen phthalate (KHP). This method involves the experimental data fitting with the theoretical titration curve TC(NLR), also developed by the INMC. TC(NLR) replaces the traditional empirical W-function (eWf), which has no chemical basis and does not account for CO2 as an impurity. The KHP content of the CRM KHP 84L from NIST was measured using the developed coulometer, resulting in 4.9069 ± 0.0090 mol kg-1 with a bias of 0.21% for the eWf, and a more accurate result of 4.8983 ± 0.0047 mol kg-1 with a bias of 0.041% for the TC(NLR). The challenges during the development of the coulometer, particularly in terms of instrumentation, as well as their impact on uncertainty, are also discussed.